Analysis of Science Teaching Material Development Needs: Teachers' Perceptions of Ethnoscience Integration in Junior High and Senior High School Science Textbooks - Putriade Rahma Yulis; Nurul Fauziah; Asyti Febliza (Universitas Pendidikan Mandalika, 2025)
Education today requires the implementation of contextual, responsive, and culturally sensitive approaches to create learning that is relevant to the daily lives of students and more inclusive. To date, research on ethnoscience in science education has primarily focused on the development of learning models, the implementation of ethnoscience in the classroom, or conceptual studies on the integration of culture in science learning. Studies that specifically analyze science textbooks as the primary learning resource are still limited and tend to be descriptive, without directly linking them to teachers' perceptions and the development of teaching materials in specific regional contexts. Therefore, this study is novel in filling this gap through an analysis of the need to develop ethnoscience-based science textbooks based on the perceptions of junior high and high school teachers in Riau Province, which provides an empirical basis for the development of teaching materials and the formulation of more contextually and locally based education policies. This study used a survey method involving 12 junior high school and high school science teachers from 12 different schools in various regions of Riau. The research instrument was a perception questionnaire from the perspective of teachers and students. Data analysis was conducted both descriptively and quantitatively, using simple statistics, and supplemented by qualitative interpretations of open-ended responses. The results showed that both teachers and students considered the integration of ethnoscience in science textbooks to be very limited, unsystematic, and lacking a strong connection between scientific concepts and local culture. The needs analysis indicated the need to develop culture-based textbooks that explicitly include the cultural context of Riau, are scientifically structured, and can strengthen the understanding of science concepts. This study has significant implications for teachers, textbook authors, and also curriculum developers, as it underscores the importance of enhancing the relevance of science learning through integration of local culture.